PENGARUH PEMELIHARAAN OVERHAUL TURBOCHARGER TERHADAP KINERJA MESIN UNIT VII PLTD AMPENAN - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2017)
Increasing number of Indonesian population and unequal distribution of population with higher densities only on certain islands rather than outside the islands, appropriate development strategies are needed in providing need for electrical resilience for the population. Frequent interactions with fuel - powered engines such as diesel engines and human resource readiness probably are reasons for government choice in using diesel powered engines (very big and medium sized diesel engines) to provide electricity on small islands and remote islands. Availability of electrical energy will create a conducive investment climate and improve welfare of the population. Lombok West Nusa Tenggara is one of small islands in Indonesia. In the area, electricity need is generated by PLTD Ampenan. One of the Ampenan diesel engines in unit VII is New Sulzer 12 ZAV 40 S equipped with double turbocharger type VTR 354. To maintain its performance, overhauls done routinely. Overhaul is a procedure performed to restore engine performance to factory standard specification value and give second age with condition worn or defective components refer to reusable parts instructions according to factory standards. This research focuses on the state of the diesel engine as a prime mover of generator before and after its turbocharger overhaul. And also, things about turbocharger overhaul and its effect on the engine.